Synaptic plasticity investigation in permalloy based channel material for neuromorphic computing - Monalisha, P. (2023)
Artificial synaptic devices capable of synchronized storing and processing of information are the critical building blocks of neuromorphic computing systems for the low-power implementation of artificial intelligence. Compared to the diverse synaptic device structures, the emerging electrolyte-gated synaptic transistors are promising for mimicking biological synapses owing to their analogous working mode. Despite the remarkable progress in electrolyte-gated synaptic transistors, the study of metallic channel-based synaptic devices remains vastly unexplored. Here, we report a three-terminal electrolyte-gated artificial synapse based on metallic permalloy as the active layer. Gating controlled, non-volatile, rewritable, and distinct multilevel conductance states have been achieved for analog computing. Representative synaptic behaviors such as excitatory postsynaptic conductance (EPSC), paired-pulse facilitation (PPF), spike amplitude-dependent plasticity (SADP), spike duration-dependent plasticity (SDDP), and long-term potentiation/depression (LTP/D) have been successfully simulated in the synaptic device. Furthermore, switching from short-term to long-term memory regimes has been demonstrated through repeated training. Benefitting from the short-term facilitation, the synaptic device can also act as a high-pass temporal filter for selective communication. This research highlights the great potential of metallic channel-based synaptic devices for future neuromorphic systems and augments the diversity of synaptic devices.